SMEs reduce the country's problems in terms of labor in Indonesia - Azhari, Azhari (Universitas Warmadewa, 2024)
One of the economic problems in a country is unemployment. Various alternative solutions are carried out by the state to reduce the unemployment rate. One of them is to increase the number of SMEs in the hope that the number of exports and investments can reduce the unemployment faced by a country. However, the problems of SMEs in Indonesia are influenced by several factors such as lack of mastery of technology, managerial and access to credit which is still difficult. This study aims at the impact of the number of SME units, exports, and investment on employment in the SME sector in Indonesia. The data used data on the number of SME units, exports, investment, and labor in SME sectors from 1997 to 2019 were sourced from the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, with a random effect model as an analysis tool. The results showed that the number of SME units, exports, and investments had an impact on employment, both partially and simultaneously. This research implies that the government should provide tax incentives for SMEs, soft skills training, strengthen the capacity of SMEs, and provide adequate access to capital. The limitations of this study are that it does not look at SMEs by type of business. Using this type of SME is a special attraction for further research.